High-density polyethylene/red mud polymer composites: Effect of UV annealing - TAŞDEMİR, MÜNİR (Certex, INCDTP-ICPI, 2016)
An investigation was carried out on the effects of red mud ratio and UV annealing treatment on the mechanical, thermal and morphological properties of high-density polyethylene (HDPE)/red mud (RM) polymer composites. Red mud, in six different concentrations (0, 10, 20, 30, 40, and 50 wt %), was added to HDPE to produce composites. The annealing UV treatment was carried out at 100°C for three different holding times: 100, 200 and 300 h. The mechanical properties, including the elastic modulus, tensile strengths, strain at tensile strength, Izod impact resistance, hardness, and melt flow index with and without an annealing UV treatment, and the thermal properties, such as the Vicat softening point, heat deflection temperature and melt-flow index, of the composites were investigated. © 2016 Certex, INCDTP-ICPI.
Keywords: High-density polyethylene; Red mud; UV annealing